Recipient rs1045642 Polymorphism Is Associated With Office Blood Pressure at 1-Year Post Kidney Transplantation: A Single Center Pharmacogenetic Cohort Pilot Study - Bouatou, Yassine; Stenz, Ludwig; Ponte, Belen; Ferrari, Serge; Paoloni-Giacobino, Ariane; Hadaya, Karine (Frontiers in Pharmacology, 2018)
Background: Corticosteroids are associated with reduced bone mineral density (BMD), as well as water and salt retention, leading to hypertension. They are substrates for P-glycoprotein, a protein coded by the highly polymorphic ABCB1 gene. We hypothesized that one ABCB1 polymorphism, rs1045642, is associated with blood pressure and BMD parameters at 1-year post kidney transplantation (KT). Methods: Rs1045642 was genotyped using pyrosequencing in 40 KT recipients. Both dominant (CC vs. CT+TT) and codominant (CC vs. CT vs. TT) genetic models (analysis of variance from linear regressions) were adjusted for confounding variables (age, sex, type of nephropathy, glomerular filtration rate, and corticosteroid use at 1 year). Results: Rs1045642 genotypes were significantly associated with systolic (SBP) and diastolic (DBP) blood pressure 1-year post-transplantation, independent of the genetic model used (adjusted codominant model: SBP p-value = 0.015, DBP p-value = 0.038; adjusted dominant model: SBP p-value = 0.003, DBP p-value = 0.011). A non-statistically significant trend was observed for an association between rs1045642 and BMD change at 1-year post-KT. Conclusions: Rs1045642 is significantly associated with higher BP 1 year after KT. Further investigations are necessary to confirm the role of rs1045642 in corticosteroid-related adverse effects.